System Kids : Adolescent Mothers and the Politics of Regulation - Silver, Lauren J. (Book collections on Project MUSE., 2015)
This title explores the daily lives of adolescent mothers as they negotiate the child welfare system to meet the needs of their children and themselves. Combining critical policy study and ethnography, and drawing on scholarship as well as her experience as a welfare programme manager, Lauren Silver demonstrates how social welfare 'silos' construct the lives of youth as disconnected, reinforcing unforgiving policies and imposing demands on women the system was intended to help.